Investigations into the Factors Influencing Maternal Mortality Among Women of Childbearing Age in Ifoyintedo Community, Yewa South Local Government Area, Ogun State (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
IntroductionMaternal mortality remains a significant global health issue, with a disproportionate burden on women in low- and middle-income countries. Despite various preventive measures, maternal deaths continue to be a leading cause of morbidity and mortality among women of childbearing age. Understanding the factors contributing to maternal mortality and the preventive measures is crucial for developing effective strategies to reduce its incidence.ObjectiveThe aim of this study was to identify and analyze the factors influencing maternal mortality among women of childbearing age in Ifoyintedo community. It also sought to examine the level of awareness of maternal mortality, its causes, and the preventive measures taken by women in this community.Method of AnalysisThis cross-sectional study surveyed 200 women of childbearing age in Ifoyintedo. Data were collected using structured questionnaires designed to assess knowledge, awareness, and preventive measures related to maternal mortality. Descriptive statistics were used to summarize the data, while chi-square tests assessed the relationship between sociodemographic characteristics and knowledge of maternal mortality.ResultsThe findings revealed that 95% of women were aware of maternal mortality, with 80% recognizing the role of high blood pressure during pregnancy (pre-eclampsia and eclampsia) as a leading cause. Early recognition and management of complications were identified as key preventive measures by 84% of the participants. Furthermore, 86% acknowledged the importance of postpartum monitoring, while 67% indicated that improving the quality of healthcare services could reduce maternal mortality. Socio-demographic factors such as educational level and marital status showed significant relationships with knowledge about maternal mortality, with p-values of 0.016 and 0.040, respectively, suggesting that higher education and marital status influence awareness.ConclusionThis study highlights the significant awareness of maternal mortality among women in Ifoyintedo, but also reveals gaps in knowledge regarding specific causes and preventive measures. Education level and marital status were found to play crucial roles in shaping women's awareness of maternal health issues. The findings emphasize the need for targeted health education programs and improved healthcare infrastructure in rural areas to reduce maternal mortality rates in the community.